(untitled) - Çilingiroglu, A. (Paris, 1975)
This book introduce background and methology, definition of the industry. Technological evaluation of the industry. Future prospects of the industry in participating countries..
Keywords: Pharmaceutical industry,Công nghiệp dược phẩm; Europe,Châu Âu